2022
DOI: 10.1037/dev0001429
|View full text |Cite
|
Sign up to set email alerts
|

“It bites!”: The transmission of negative information about snakes and spiders through a naturalistic picture book interaction.

Abstract: Snakes and spiders are two of the most commonly feared animals worldwide, yet we know very little about the mechanisms by which such fears are acquired. We explored whether negative information about snakes and spiders from parents shapes children's fear beliefs. Study 1 included 27 parents (22 mothers, five fathers) and children (12 female, 15 male, M age = 5.33 years, 18 White, one Hispanic, eight more than one race). Most parents reported having an advanced degree (78%) and an annual household income of abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…The empirical literature on the use of conservation messaging to advocate for biodiversity conservation is limited, and current findings are contradictory or unclear [ 57 59 ]. To elucidate ambiguous results, recent literature proposes that identification of target audiences and examination of individuals’ qualities is key to understanding the effectiveness of conservation messages [ 5 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…The empirical literature on the use of conservation messaging to advocate for biodiversity conservation is limited, and current findings are contradictory or unclear [ 57 59 ]. To elucidate ambiguous results, recent literature proposes that identification of target audiences and examination of individuals’ qualities is key to understanding the effectiveness of conservation messages [ 5 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…This irrational belief could explain their relatively high fear rating detected in this study. It was demonstrated that attitudes towards particular animals can be a subject of social transmission in childhood (Reider et al 2022 ). Nevertheless, lizards were still considerably less frightening stimuli than snakes.…”
Section: Discussionmentioning
confidence: 99%
“…However, using positive information to talk about animals like snakes is very uncommon in naturalistic parent-child conversations. As mentioned above, several studies have demonstrated that parents use a disproportionately larger amount of negative than positive information about snakes (Conrad et al, 2021b;Reider et al, 2022), leaving children with relatively few (or no) positive attributes about snakes. Indeed, parents may be reluctant to provide positive information about snakes because of the threatening properties associated with many species of snakes.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that fear of a novel animal increases after hearing negative information (e.g., describing animals as being dirty or dangerous), and decreases after hearing positive information (e.g., describing animals as being cuddly and friendly; Field and Lawson, 2003;Muris et al, 2003; see Muris and Field, 2010 for a review). Naturalistic studies of parent-child conversations about animals have further shown that parents and children use more negative language when talking about snakes in everyday conversations with children, and they also report greater fear of snakes compared to other animals (e.g., Conrad et al, 2021b;Reider et al, 2022), further suggesting that negative information may be one pathway through which children learn to fear snakes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation